2013
DOI: 10.1371/journal.pone.0078659
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Numerical Simulations to Experiments for Atomization in a Jet Nebulizer

Abstract: The development of jet nebulizers for medical purposes is an important challenge of aerosol therapy. The performance of a nebulizer is characterized by its output rate of droplets with a diameter under 5 µm. However the optimization of this parameter through experiments has reached a plateau. The purpose of this study is to design a numerical model simulating the nebulization process and to compare it with experimental data. Such a model could provide a better understanding of the atomization process and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…However, when passed through the small cavity, the velocity increases by over 100 times, or between 476 and 579 m/s. This velocity is consistent with the numerical and experimental results reported by Lelong et al [19], a study of the atomization process in a jet nebulizer. According to the Venturi effect principle, the higher the velocity of a fluid, the lower the pressure.…”
Section: Resultssupporting
confidence: 92%
“…However, when passed through the small cavity, the velocity increases by over 100 times, or between 476 and 579 m/s. This velocity is consistent with the numerical and experimental results reported by Lelong et al [19], a study of the atomization process in a jet nebulizer. According to the Venturi effect principle, the higher the velocity of a fluid, the lower the pressure.…”
Section: Resultssupporting
confidence: 92%
“…It can be seen that the general trend in Figure 6 a agrees with that of Figure 6 b [ 18 ]. However, the distribution in Figure 6 a is skewed towards small coupling energy drops.…”
Section: Resultssupporting
confidence: 72%
“… ( a ) Count of coupling energy drops during the test of water particles with our device. Coupling energy drops smaller than 5% are considered noise and excluded from the count; ( b ) Particle size distribution in a nebulizer’s output measured with Malvern’s Spraytec particle counter [ 18 ]. …”
Section: Figurementioning
confidence: 99%
“…In addition, parameters describing primary atomization values for solid cone or hollow cone type models will also be determined. While extensive studies of spray atomization exist, these have covered high-pressure applications found in combustion and industrial sprays [22,23]. For nasal sprays that exhibit low-pressures there is a lack of information.…”
Section: Introductionmentioning
confidence: 99%